The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1111/mec.12891
|View full text |Cite
|
Sign up to set email alerts
|

Early and late response of Nematostella vectensis transcriptome to heavy metals

Abstract: Environmental contamination from heavy metals poses a global concern for the marine environment, as heavy metals are passed up the food chain and persist in the environment long after the pollution source is contained. Cnidarians play an important role in shaping marine ecosystems, but environmental pollution profoundly affects their vitality. Among the cnidarians, the sea anemone Nematostella vectensis is an advantageous model for addressing questions in molecular ecology and toxicology as it tolerates extrem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 84 publications
1
37
0
Order By: Relevance
“…In Cnidaria, AP-1 was suggested to mediate stress responses such as upon elevation in seawater temperature and injury as well as exposure to heavy metals, which we previously showed to affect fos transcript [25, 26, 28, 54]. Here, we show the involvement of MAPKs in the regulation of AP-1 transcripts fos1 and jun1 in the presence of Hg.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…In Cnidaria, AP-1 was suggested to mediate stress responses such as upon elevation in seawater temperature and injury as well as exposure to heavy metals, which we previously showed to affect fos transcript [25, 26, 28, 54]. Here, we show the involvement of MAPKs in the regulation of AP-1 transcripts fos1 and jun1 in the presence of Hg.…”
Section: Discussionmentioning
confidence: 64%
“…RNA was extracted from Hg-treated and untreated anemones using Tri-reagent (Sigma-Aldrich) and purified as described previously [25]. qPCR was performed using the StepOnePlus Real-Time PCR System (Applied Biosystems) and β-actin was used as an internal control as described previously [25].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ron Elran and Maayan Raam (Lotan laboratory, University of Haifa, Israel) presented a study of the transcriptomic responses of Nematostella following exposure to mercury, cadmium, copper and zinc (Elran et al, 2014). Broadly, they found that only a few genes were differentially expressed in response to all four metals and that copper- and mercury-treated anemones exhibited expression patterns that were relatively similar to one another.…”
Section: Environmental Interactionsmentioning
confidence: 99%